Modeling Analysis of the Upper Limit Water Level Mechanism in the Upstream Reservoir of a Dam Embankment. (29th November 2020) - Xu, Shiqiang; Chen, Chaoran; Xu, Fu; Li, Jie; Zhang, Zhipeng; Xu, Tianyu; Zhu, Linxuan
Abstract : The dam embankment (DE) is a highway structure used in the Loess Plateau to integrate the functions of a highway embankment and a dam. This paper studies the upper limit water level mechanism of the reservoir in the upstream of the DE to determine the criterion for setting upper culverts on the DE. A reservoir model is first established, and then the replenishment and loss of the reservoir water is simulated. The principle of water balance is employed to obtain water level formulas for the reservoir. Finally, an engineering example is used to verify the upper limit water level mechanism. The results show that the water level of the reservoir fluctuates near an ideal balance water level and an upper limit water level exists. Moreover, the upper limit water level has no relation to the water storage time, and is only related to the reservoir shape with big upper and small bottom, the small amount of water entering the reservoir each year, and the large water loss caused by evaporation and leakage. The upper culvert setting criterion is obtained through the upper limit water level mechanism, and it will provide important reference significance for the necessity of the DE culvert setting.